Nekateri novejši ekonomskogeografski pojmi - Vrišer, Igor (Geografski vestnik, 2001)
The world economic development in the last twenty years have brought forward also in the economic geography some new notions. They represent important processes and changes in the world economy and especially in the organization and dislocation of the manufacturing. The applied notions are deindustrialization, fordism, postfordism, globalization, global players and flexible system of manufacturing.
Keywords: ekonomska geografija; strokovna terminologija; Slovene; slovenščina